Immobilization of hydroxyapatite on polyetherketoneketone surfaces for improved cell adhesion; Materials Letters; Vol. 362 - Goreninsky (Goreninskii) S. I. Semen Igorevich; Akimchenko I. O. Igor Olegovich; Konoplyannikov M. A. Mikhail Anatoljevich; Sudarev E. A. Evgeniy Aleksandrovich; Timashev P. S. Peter; Zvyagin A. V. Andrey Vasiljevich; Tverdokhlebov S. I. Sergei Ivanovich (2024, 2024)
Title screen